Fault-controlled carbonate cementation: A case study from Eocene turbidite-delta sandstones (Dongying Depression) and implication for hydrocarbon migration. (July 2021) - Luan, Guoqiang; Azmy, Karem; Dong, Chunmei; Lin, Chengyan; Ren, Lihua; Shi, Changying
Abstract: The subsurface distribution of carbonate cements in sandstones is cornerstone in understanding the fluid regime and origin of cements to shed the light on hydrocarbon migration. Petrography, cuttings, cores, well logs, and seismic data were integrated to better understand the distribution of carbonate cements in the Eocene turbidite-delta sandstones of the Dongying Depression. Petrographic examinations (including cathodoluminescence, CL) reveal that the carbonate cements are mainly calcite with minor ankerite that precipitated in deep burial settings. The significant abundance of carbonate cements near fault zones implies migration of fluids from deep settings through late fractures developed by compaction under deep burial conditions. The extent of carbonate-cemented zones may reach hundreds of meters away from the faults, while scatter carbonate cements are much more extensive. The relationship of pervasive and scattered calcites with oil-bearing sandstones suggests that the pervasive calcite cementation started as soon as the hydrocarbon and brine mixed fluid were displaced while the scatter calcite cements came after. The occurrence of abundant carbonate-cemented zones in the delta front oil-free sandstone intervals suggests possible hydrocarbon migration to the overlying sandstone units. Highlights: Subsurface distribution of carbonate cements is mapped by integrated methods. The late carbonate cementation is fault-controlled from upwelling fluid. Major calcite cemented zones occurred synchronously with hydrocarbon charging. The late calcite cementation can provide implications for hydrocarbon migration.